Strategies To Increase People's Business Credit - Asrin Tandi (Pelopor Publikasi Akademika, 2024)
This study aims to determine and analyze strategies in increasing People's Business Credit. Type of Research is a Type of Qualitative Research. This research was conducted at Bank Sulsebar Mamasa Branch. Research data sources from primary data and secondary data. Data collection methods through observation, interviews and documentation. This research uses qualitative descriptive analysis methods and SWOT analysis. The results of this study show that: The strategy in providing People's Business Credit in increasing customers is carried out by socializing to the public about the superior products of People's Business Credit, improving the process of providing People's Business Credit so that it is not slow in providing certainty in providing credit, selective in lending and providing assistance in business development for People's Business Credit debtors. The strategy in providing People's Business Credit in increasing customers is carried out by socializing to the public about superior products People's Business Credit, improving the process of providing People's Business Credit, so as not to be slow in providing certainty in providing credit, selective in lending and providing assistance in business development for debtors of People's Business Credit.